EFFECT OF DIFFERENT REGIME OF WATERING ON MILK YIELD AND MILK CONSTITUENTS IN LACTATING MURRAH BUFFALOES - Singh, akhilesh; Jain, Aklank; Lakhani, G.P (Indian Journal of Animal Production and Management, 2017)
Seventy to ninety percent of the total water consumed by the lactating cow is drinking water. Approximately26 to 34 percent of total water intake is used in milk secretion. In India, generally watering of the animalis done after milking in the morning and before milking in the evening and rest of the time animal remainswithout drinking water which adversely affect in milk production. Therefore, present study was undertakento find out the effect of different regime, of watering were studied on milk yield and milk constituents inlactating Murrah buffalos. The animals were subjected to four regime of watering, adlib (Group I), beforemilking (Group II), after milking (Group III) and before and after milking (Group IV). Results revealed that,the average daily milk yield was highest in group II (8.96 liter) and differed significantly (P